Peningkatan Hasil Belajar Menggunakan Model Group Investigation Pada Pembelajaran Tematik Terpadu di Sekolah Dasar - Suryaningsih, Ade; Indrawati, Tin (Universitas Negeri Padang, 2023)
This research is motivated by the low learning outcomes of students in integrated thematic learning caused by several aspects. These aspects include aspects of planning and implementing learning. This study aims to describe the increase in student learning outcomes using the model Group Investigation in integrated thematic learning in Class V B of Bandar Buat 09 Elementary School, Padang City. This type of Classroom Action Research uses qualitative and quantitative approaches. The research used two cycles consisting of four stages, namely planning, implementing, observing, and reflecting. The subjects needed are researchers, homeroom teachers, and up to 24 students. The results of Cycle I lesson plans were 82.9% (C) and then increased in Cycle II by 95.4% (A). Assessment of the learning process in Cycle I reached 87.45% (B) and increased in Cycle II by 93.7% (A). The learning outcomes of the knowledge aspect of Cycle I was 75.7 (C) then rose to 93.9 (A) in Cycle II. Furthermore, the learning outcomes of the skills aspects of Cycle I were 81.3 (C) increasing to 94.7 (A) in Cycle II. So, it can be said the use of the model Group Investigation is able to increase the learning outcomes of students in integrated thematic learning in Class V B of Bandar Buat 09 Elementary School, Padang City.